Changes in Plasma Lipid Levels and Antioxidant Activities in Rats after Supplementation of Obtusifolin - Zhuang, Si-Yi; Wu, Miao-Li; Wei, Peng-Jv; Cao, Zhi-Ping; Xiao, Peng; Li, Chu-Hua (Planta Medica, 2016)
Obtusifolin, an anthraquinone from Cassia obtusifolia seeds, has been reported to reduce blood lipid levels in diabetic rats induced by streptozocin. However, it remains unclear whether obtusifolin possesses a lipid-lowering effect on hyperlipidemia caused by a high-fat diet. Moreover, hyperlipidemia is known to impair the endothelial function by causing oxidative stress. Therefore, in the present study, we investigated the antidyslipidemic and antioxidant effects of obtusifolin in hyperlipidemic rats induced by a high-fat diet. Rats with oral fat emulsion were used as our hyperlipidemic model. We measured the body weight of the rats, serum total cholesterol, triglycerides, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol, as well as nitric oxide, malondialdehyde, and superoxide dismutase. Our results showed that oral obtusifolin application significantly reversed the changes induced by hyperlipidemia in body weight, total cholesterol, triglyceride, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol. Furthermore, obtusifolin treatment increased serum superoxide dismutase and nitric oxide, but reduced malondialdehyde. Collectively, our findings suggest that obtusifolin may improve hyperlipidemia by enhancing antioxidant activity. This study indicates a potential therapeutic importance of obtusifolin for ameliorating lipid dysfunction induced by a high-fat diet.
Keywords: Cassia obtusifolia; obtusifolin; hyperlipidemia; high-fat diet; antioxidation